GIS APPLICATION WHEN USING PHOSPHOGYPTIC COMPOSITIONS TO IMPROVE MELIORATIVE SOIL PROPERTIES - Yigitalieva R.R; Komilov Q.O; KurbanovaA. Dj (International Engineering Journal For Research & Development, 2020)
The article presents the possibilities of using geographic information systems in assessing the performance of the region’s economy. Electronic maps created on the basis of the “Resource Potential of Semi-Saline and Saline Soils” database help to investigate and describe the spatial differentiation of the region’s economy, the nature and relationship of business entities, and to identify environmental management features. Some indicators that characterize the main trends in the agriculture of Tuva are reflected. The application of the capabilities of geographic information technologies ensures the comprehensiveness and visibility of the presentation of information. The article deals with the use of phosphogypsum for effective dressing in various soil and climatic zones for cereals, vegetables, industrial and other crops, to increase the yield of cotton and the technological quality of its fiber. That the use of phosphogypsum as a chemical ameliorant improves the chemical, physical and water - physical properties of the soil.